Lyve-1 deficiency enhances the hepatic immune microenvironment entailing altered susceptibility to melanoma liver metastasis: research - Jauch, Anna Sophia; Wohlfeil, Sebastian A.; Weller, Céline; Dietsch, Bianca; Häfele, Verena; Stojanovic, Ana; Kittel, Maximilian; Nolte, Hendrik; Cerwenka, Adelheid; Neumaier, Michael; Schledzewski, Kai; Sticht, Carsten; et al. (Cancer cell international, 2022)
Hyaluronan receptor LYVE-1 is expressed by liver sinusoidal endothelial cells (LSEC), lymphatic endothelial cells and specialized macrophages. Besides binding to hyaluronan, LYVE-1 can mediate adhesion of leukocytes and cancer cells to endothelial cells. Here, we assessed the impact of LYVE-1 on physiological liver functions and metastasis. Mice with deficiency of Lyve-1 (Lyve-1-KO) were analyzed using histology, immunofluorescence, microarray analysis, plasma proteomics and flow cytometry. Liver metastasis was studied by intrasplenic/intravenous injection of melanoma (B16F10 luc2, WT31) or colorectal carcinoma (MC38). Hepatic architecture, liver size, endothelial differentiation and angiocrine functions were unaltered in Lyve-1-KO. Hyaluronan plasma levels were significantly increased in Lyve-1-KO. Besides, plasma proteomics revealed increased carbonic anhydrase-2 and decreased FXIIIA. Furthermore, gene expression analysis of LSEC indicated regulation of immunological pathways. Therefore, liver metastasis of highly and weakly immunogenic tumors, i.e. melanoma and colorectal carcinoma (CRC), was analyzed. Hepatic metastasis of B16F10 luc2 and WT31 melanoma cells, but not MC38 CRC cells, was significantly reduced in Lyve-1-KO mice. In vivo retention assays with B16F10 luc2 cells were unaltered between Lyve-1-KO and control mice. However, in tumor-free Lyve-1-KO livers numbers of hepatic CD4+, CD8+ and regulatory T cells were increased. In addition, iron deposition was found in F4/80+ liver macrophages known to exert pro-inflammatory effects. Lyve-1 deficiency controlled hepatic metastasis in a tumor cell-specific manner leading to reduced growth of hepatic metastases of melanoma, but not CRC. Anti-tumorigenic effects are likely due to enhancement of the premetastatic hepatic immune microenvironment influencing early liver metastasis formation.
Gesehen am 12.06.2023